2007
DOI: 10.1007/s11738-007-0112-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of endogenous and exogenous RNases on the variation of pollen cytosolic-free Ca2+ in Pyrus serotina Rehd

Abstract: The objective of this study was to examine whether S-RNase plays a specific role in the pre-germinated Pyrus pollen. Effects of exogenous RNase and endogenous S-RNase on concentration of cytosolic-free calcium ([Ca 2+ ] i ) variation of pre-germinated Pyrus pollen were studied. [Ca 2+ ] i variation caused by different RNases were complex. In 1 h after being cultured, exogenous RNase, RNase T 1 and RNase A, and endogenous incompatible 'Hohsui' RNase promoted the [Ca 2+ ] i of 'Hohsui' pollen. Acid proteins of '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…We detected three ABC transporters in which the expression profile of the ABCA gene was similar to MdABCF [ 54 ] and significantly associated with S-RNase transport. Calcium is the second messenger of cell signal transduction, and previous studies have confirmed that the Ca 2+ gradient is involved in the self-incompatibility of pears [ 31 , 40 ]. We have detected three genes related to the formation of calcium ion gradients and its signal transduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We detected three ABC transporters in which the expression profile of the ABCA gene was similar to MdABCF [ 54 ] and significantly associated with S-RNase transport. Calcium is the second messenger of cell signal transduction, and previous studies have confirmed that the Ca 2+ gradient is involved in the self-incompatibility of pears [ 31 , 40 ]. We have detected three genes related to the formation of calcium ion gradients and its signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…This involves a complex genetic mechanism, and the display of the complete trait of self-incompatibility not only depends on the S-site genes (pistil S gene and pollen S gene) but, also, several modifier genes associated with complex mechanisms that have been gradually explored [ 29 ]. These modifier genes are involved in multiple signal transduction systems [ 29 ], for example, calcium ion signaling [ 29 , 30 , 31 ], reactive oxygen signaling [ 32 ], hormone signaling [ 33 ], inositol phosphate signaling [ 34 , 35 ], biochemical metabolism processes [ 36 ], programmed cell death (PCD) [ 32 , 37 ], and cell wall and cytoskeletal construction [ 28 , 38 , 39 , 40 , 41 ]. These modifiers, distributed in a determined location of the chromosome, will affect the intensity of self-incompatibility to varying degrees, and be directly reflected in the fruit-set rate.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed a protocol for the successful isolation of spheroplasts from the pollen tube of the pear, identified a hyperpolarization‐activated cation channel using the patch‐clamp technique (Qu et al. , 2007) and discovered the relationship between the Ca 2+ ‐permeable channels of the pollen tube and self‐S‐RNase activity (Xu et al. , 2007).…”
Section: Introductionmentioning
confidence: 99%